2022
DOI: 10.32479/ijeep.12497
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Data Inflation Energy and Gasoline Price by Vector Autoregressive Model

Abstract: The study of multivariate time series data analysis has become many topics of research in the fields of economics and business. In the present study, we will analyze data energy inflation and gasoline prices of Indonesia over the years from 2014 to 2020. The purpose of this study is to obtain the best model of the dynamic relationship between inflation and gasoline prices. The dynamic modeling that will be used in this research is modeling using the Vector Autoregressive (VAR) model. From the analysis results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…De la misma forma, Bullard (2011) sostiene que, dado que los viajes a la gasolinera y al supermercado son algunas de las experiencias de compra más frecuentes para muchos estadounidenses, no es útil para la Reserva Federal (la Fed) excluir todos esos precios de la consideración en la formación de la política monetaria. Nairobi et al (2022) analizan la relación dinámica entre la inflación energética y los precios de la gasolina en Indonesia en el periodo comprendido entre 2014 y 2020 con un modelo vectorial autorregresivo (var, Vector Autoregressive). Los resultados muestran que el mejor modelo es el var con orden 3 [var(3)] y encuentran una fuerte influencia del precio de la gasolina en la inflación de la energía.…”
Section: Revisión Bibliográficaunclassified
“…De la misma forma, Bullard (2011) sostiene que, dado que los viajes a la gasolinera y al supermercado son algunas de las experiencias de compra más frecuentes para muchos estadounidenses, no es útil para la Reserva Federal (la Fed) excluir todos esos precios de la consideración en la formación de la política monetaria. Nairobi et al (2022) analizan la relación dinámica entre la inflación energética y los precios de la gasolina en Indonesia en el periodo comprendido entre 2014 y 2020 con un modelo vectorial autorregresivo (var, Vector Autoregressive). Los resultados muestran que el mejor modelo es el var con orden 3 [var(3)] y encuentran una fuerte influencia del precio de la gasolina en la inflación de la energía.…”
Section: Revisión Bibliográficaunclassified
“…(Samanta and Zadeh, 2012;Partalidou et al, 2016;Raza et al, 2016;Arfaoui and Rejeb, 2017;Wei and Guo, 2017;Karhan and Aydın, 2018;Pandey and Vipul, 2018;Alio et al, 2019;Singhal et al, 2019;Kumar et al, 2019;Majidli and Guliyev, 2020;Kumar et al, 2021;Kumau et al, 2020;Gherghina et al, 2020;Humbatova et al, 2020;Karakuş, 2021). Some of the empirical studies employed vector autoregressive model (VAR) (Ding et al, 2016;Chkili, 2022;Grabias, 2022;Nairobi et al, 2022;Kelesbayev et al, 2022). However, not a single study was able to explain the specific relationship between gold, crude oil, and the stock market (Uthumrat, 2022 p.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is an extension of the univariate autoregressive model, and has been widely used in various fields, including finance, psychology, and medicine analysis (Zivot & Wang, 2006;Halsbeck, Bringmann, & Waldorp, 2020;Khan, Saeed, & Ali, 2020). VAR model has gained significant attention in recent years for its usefulness in describing the dynamic behaviour of financial time series and for forecasting their future values (Russel, Pratama, Wamiliana, & Usman, 2022). As a regression model, VAR has been widely applied in various fields, including modelling time dependence in multivariate time series data (Davis, Zang, & Zheng, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The study uses VAR modelling, and the best model is found to be VAR with order 3. Further analysis, including Granger causality, impulse response function, and forecasting, will be conducted based on the best model VAR(3) (Usman, Paujiah, Russel , Nairobi, & Pratama, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%